Guidelines for Self-directed Learning Ability Development of Social Development and Human Security Volunteers in Nakhon Ratchasima Provinc - Lertvichai, Ratda (Ratchaphruek Journal, 2021)
The purpose of this research were to: 1) Study self-directed learning ability of Social Development and Human Security Volunteers in Nakhon Ratchasima Province and; and 2) Propose guidelines to develop self-directed learning ability of Social Development and Human Security Volunteers in Nakhon Ratchasima Province. The samples consisted of 354 Social Development and Human Security Volunteers in Nakhon Ratchasima Province in 2019, and were selected from 4270 population by stratified sampling. The research instruments were an interview form, a self-directed learning ability questionnaire, an assessment form, and a confirmation form for guidelines to self-directed learning ability. Data were analyzed by frequency, percentage, means, standard, and content analysis. The results of the research were: 1. Social Development and Human Security Volunteers in Nakhon Ratchasima Province had high self-directed learning abilities, as a whole, and individual aspects. 2. Guidelines to develop self-directed learning ability consisted of 3 development approaches: 1) studying information from necessary documents, 2) training and field trips, and 3) organizing conferences and exhibitions to present creative works.